SARS-CoV-2 indoor contamination: considerations on anti-COVID-19 management of ventilation systems, and finishing materials in healthcare facilities - Gola, M.; Caggiano, G.; De Giglio, O.; Napoli, C.; Diella, G.; Carlucci, M.; Carpagnano, L. F.; D'Alessandro, D.; Joppolo, C. M.; Capolongo, S.; Montagna, M. T. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Many of the devastating pandemics and outbreaks of last centuries have been caused by enveloped viruses. The recent pandemic of Coronavirus disease 2019 (COVID-19) has seriously endangered the global health system. In particular, hospitals have had to deal with a frequency in the emergency room and a request for beds for infectious diseases never faced in the last decades. It is well-known that hospitals are environments with a high infectious risk. Environmental control of indoor air and surfaces becomes an important means of limiting the spread of SARS-CoV-2. In particular, to preserve an adequate indoor microbiological quality, an important non-pharmacological strategy is represented by Heating, Ventilation and Air Conditioning (HVAC) systems and finishing materials. Starting from the SARS-CoV-2 transmission routes, the paper investigates the hospital risk analysis and management, the indoor air quality and determination of microbial load, surface management and strategies in cleaning activities, HVAC systems’ management and filters’ efficiency. In conclusion, the paper suggests some strategies of interventions and best practices to be taken into considerations for the next steps in design and management.